2012
DOI: 10.1103/physrevb.86.224510
|View full text |Cite
|
Sign up to set email alerts
|

Coherent Cooper-pair pumping by magnetic flux control

Abstract: We introduce and discuss a scheme for Cooper-pair pumping. The scheme relies on the coherent transfer of a superposition of charge states across a superconducting island and is realized by adiabatic manipulation of magnetic fluxes. Differently from previous implementations, it does not require any modulation of electrostatic potentials. We find a peculiar dependence of the pumped charge on the superconducting phase bias across the pump and that an arbitrarily large amount of charge can be pumped in a single cy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The instantaneous cross-correlation is always negative, as required. 23 For small amplitudes it shows a resonant contribution at ✏ ⇡ 0, when the addition energy of adding an electron to the empty dot is equal to the electrochemical potential, and at ✏ ⇡ U , when a second electron can be added. These two contributions coincide, when the Coulomb interaction is zero (see blue, dashed line).…”
Section: A Instantaneous Contribution To the Noisementioning
confidence: 99%
See 1 more Smart Citation
“…The instantaneous cross-correlation is always negative, as required. 23 For small amplitudes it shows a resonant contribution at ✏ ⇡ 0, when the addition energy of adding an electron to the empty dot is equal to the electrochemical potential, and at ✏ ⇡ U , when a second electron can be added. These two contributions coincide, when the Coulomb interaction is zero (see blue, dashed line).…”
Section: A Instantaneous Contribution To the Noisementioning
confidence: 99%
“…[7][8][9][10][11][12][13] In addition to the current signal, knowledge about the noise created during a pumping cycle is vitally important, for instance in metrology to investigate the quantization limitations of the pump, [14][15][16] and also as a tool to detect signatures for emission of coherent electron packets. 17,18 Recently, there has also been strong interest in pumping due to quantum-interference effects, [19][20][21][22][23] where the pumped charge is not quantized. In this context, it has been shown that the pumped charge may be used as a spectroscopic tool that reveals features beyond time-independent measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Hereafter we focus on the single electron transport between the normal metal leads and do not consider possible magnetic pumping based on the use of Cooper pair sluices in Josephson systems with S electrodes. 13 The size of the Coulomb blockaded S island is assumed to be of the order of several coherence lengths ξ so that applying an external magnetic field we can introduce at least one vortex in this island. The electronic transport through this device can be described by a standard rate equation accounting for parity effects.…”
Section: And 5 and References Therein)mentioning
confidence: 99%
“…Applying a constant bias voltage V to the SET, one can convert this modulation of the charge state into unidirectional charge pumping. Note that another version of magnetic field induced pumping can be realized in the Cooper pair sluices suggested for Josephson structures with S electrodes [12]. The above picture of the vortex controlled parity effect can change at temperatures less than the minigap ω 0 in the spectrum of quasiparticles trapped in the vortex core [13].…”
mentioning
confidence: 97%